2003
DOI: 10.1071/sr02100
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate ammonification and its relationship to the accumulation of ammonium in a Vertisol subsoil

Abstract: High concentrations of ammonium (up to 270 kg N/ha) have been observed in a Vertisol soil below 1 m depth near Warra in south-east Queensland. This study examined the possibility that increased water movement into the subsoil after the removal of native vegetation, and a subsequent increase in periods of waterlogging, could have triggered nitrate ammonification and be responsible for the production of ammonium. Two incubation experiments were conducted to test this hypothesis. The first involved the incubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…The significant correlations between NO 3 − reduction and NH 4 + recovery are in agreement with findings by Page et al . (2003) and Tusneem (1970), that reported that NO 3 − is reduced to NH 4 + under O 2 -limited conditions, similarly to the current experiment. This process requires an electron source generally in the form of C; hence there are significant differences in NH 4 + appearance and NO 3 − reduction as influenced by different C sources (Mohan and Cole, 2007; Soussana and Lemaire, 2014).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The significant correlations between NO 3 − reduction and NH 4 + recovery are in agreement with findings by Page et al . (2003) and Tusneem (1970), that reported that NO 3 − is reduced to NH 4 + under O 2 -limited conditions, similarly to the current experiment. This process requires an electron source generally in the form of C; hence there are significant differences in NH 4 + appearance and NO 3 − reduction as influenced by different C sources (Mohan and Cole, 2007; Soussana and Lemaire, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…This process occurs in anaerobic conditions; however, its importance in soils remains uncertain (Yonebayashi and Hattori, 1980). The significant correlations between NO 3 − reduction and NH 4 + recovery are in agreement with findings by Page et al (2003) and Tusneem (1970), that reported that NO 3…”
Section: Ranking the Reactivity Of Carbon Compoundssupporting
confidence: 88%
“…The soil oxidation state is a principal factor that influences the importance of DNRA compared to denitrification (Matheson et al, 2002;Brunel et al, 1992) with DNRA by bacteria and fungi occurring under more reducing (anoxic) conditions (Takaya, 2002;Yin et al, 2002;Page et al, 2003). On the other hand, other studies showed that DNRA is less sensitive to variable redox conditions (Pett-Ridge et al, 2006) and less sensitive to O 2 than denitrification (Fazzolari et al, 1998).…”
Section: Environmental Conditions For Dnramentioning
confidence: 99%
“…The studies by Ambus et al (1992) and Dhondt et al (2003) both point to the occurrence of DNRA under more reduced conditions compared to denitrification. However, some studies indicated that DNRA and denitrification can occur simultaneously in soil (Paul and Beauchamp, 1989;Morley and Baggs, 2010), possibly in different micro-sites that differ in redox state. Furthermore, in contrast to Ambus et al (1992), slurry incubations with soil from a riparian zone by Davis et al (2008) resulted in higher DNRA rates in the surface soil (0-15 cm) compared to sub-soil (130-155 cm).…”
Section: N Labelling To Confirm Dnra Occurrencementioning
confidence: 99%
“…This was supported by the significantly higher pheophytin-a concentrations found in surface sediments at this site in summer 2003 (11.4±3.6 mg m −2 ) compared with those in summer 2002 (3.7±0.4 mg m −2 ). In addition, Page et al (2003) state that the anoxic conditions of sediments may enhance the sediment nitrate reduction (i.e., denitrification and dissimilatory nitrate to ammonia, DRNA) and DRNA may be favored when conditions are sufficiently reduced and electron acceptors are in sufficiently short supply, so the reduction of nitrate to ammonium becomes necessary. Such highly reduced conditions may have developed at this site during summer 2003 to allow a rapid DRNA rate to occur, leading to a high ammonium NH þ 4 release from sediments and low NO À 3 + NO À 2 uptake rate.…”
Section: Temporal (Diel and Seasonal) Variations Of Din Fluxes Acrossmentioning
confidence: 98%